2020
DOI: 10.1186/s40478-020-00920-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of aquaporin 4-reactive antibodies in Lewis rats immunized with aquaporin 4 mimotopes

Abstract: Most cases of neuromyelitis optica spectrum disorders (NMOSD) harbor pathogenic autoantibodies against the water channel aquaporin 4 (AQP4). Binding of these antibodies to AQP4 on astrocytes initiates damage to these cells, which culminates in the formation of large tissue destructive lesions in the central nervous system (CNS). Consequently, untreated patients may become permanently blind or paralyzed. Studies on the induction and breakage of tolerance to AQP4 could be of great benefit for NMOSD patients. So … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Therefore, instead of using recombinant PmAqp, we designed a peptide that contains both a T cell epitope and a conserved functional B cell epitope for immunization ( 17 ). Recently, Tsymala et al ( 36 ) reported a rat model that produces AQP4-reactive Abs by immunization with AQP4 mimotopes. These researchers screened a phage display peptide library to search for AQP4 mimotopes recognized by pathogenic AQP4-specific Abs from patients with neuromyelitis optica spectrum disorders ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, instead of using recombinant PmAqp, we designed a peptide that contains both a T cell epitope and a conserved functional B cell epitope for immunization ( 17 ). Recently, Tsymala et al ( 36 ) reported a rat model that produces AQP4-reactive Abs by immunization with AQP4 mimotopes. These researchers screened a phage display peptide library to search for AQP4 mimotopes recognized by pathogenic AQP4-specific Abs from patients with neuromyelitis optica spectrum disorders ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tsymala et al ( 36 ) reported a rat model that produces AQP4-reactive Abs by immunization with AQP4 mimotopes. These researchers screened a phage display peptide library to search for AQP4 mimotopes recognized by pathogenic AQP4-specific Abs from patients with neuromyelitis optica spectrum disorders ( 36 ). Our approach to identify a mimotope in a homologous bacterial protein was proven to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…AQP4 antibody production was induced with active immunization in Lewis rats using AQP4 mimotopes, which mimic parts of the extracellular loops of AQP4 (ref. 124 ). Some work was also done with T cell transfer models in which highly encephalitogenic AQP4 268–285 -specific T cells infiltrated the CNS and reproduced some clinical features of NMO 77 .…”
Section: Pathogenicity Of Autoantibodiesmentioning
confidence: 99%
“…Rats immunised with mimotopes of conformational AQP4 epitopes produce AQP4 Ab detectable in sensitive cell‐based assays; however, no concurrent pathology was observed 218 …”
Section: Pathogenic Mechanisms In Autoimmune Demyelinationmentioning
confidence: 99%